Understanding How Family Science Interns Conceptualize Social Justice. (3rd September 2016) - Garcia‐Reid, Pauline; van Eeden‐Moorefield, Bradley; Forenza, Brad; Reid, Robert J.; Eckert, Caitlin; Lardier, David T.
Abstract : This study examined the connection between social justice and internships in Human Development and Family Science. In particular, the study sought to provide additional clarity to current conceptualizations of social justice by adding the voices of undergraduate family science students. In‐depth qualitative interviews were conducted with 20 family science students who completed an internship that was part of a federally funded HIV/substance abuse prevention initiative. The initiative took place in an economically disadvantaged city in the northeast. Eleven themes emerged from the data and were organized according to the sensitizing concepts of (i) conceptions of social justice; (ii) exposure to social justice; (iii) synthesis of knowledge. Implications for education and training are discussed.